Job stressors and burnout among clinical nurses: a moderated mediation model of need for recovery and career calling - Tingting Jin; Yaoying Zhou; Leigang Zhang (BMC, 2023)
Abstract Background Burnout is a major concern in healthcare professions. Although theory and empirical evidence support the relationship between job stressors and burnout, the question remains how and when the job stressors are related to burnout. Based on conservation of resources theory and effort recovery model, the current study aimed to provide a deeper understanding of the effect of job stressors on burnout by investigating the mediating role of need for recovery and the moderating role of career calling. Methods A cross-sectional online survey was conducted among 709 nurses enrolled from eight public hospitals in China. The Work Stressors Scale, Psychological Detachment Scale, Brief Calling Scale, and Maslach Burnout Inventory were used to collect data. Hierarchical regression analysis with bootstrapping procedure was performed to test the proposed model. Results The results showed that need for recovery mediated the job stressors-burnout relationship, and that high career calling buffered against the relationships between job stressors and need for recovery and burnout. Furthermore, the result revealed a moderated mediation model that career calling buffered the indirect effect of job stressors on burnout through need for recovery. Conclusions Our findings suggest that environmental demands and personal resource are important antecedents of nurses' burnout. Career calling as personal resources can serve as a protective factor that guards against burnout. Thus, nursing managers can reduce nurse burnout by focusing on effective strategies related to recovery experiences, as well as investing in training career calling.